Percepções e expectativas de professores universitários sobre a formação continuada - Souza, Isilda Guimarães de (2019)
Planning the exercise of teaching in Higher Education Institutions in contemporary societies, plagued by their rapid transformations, requiring a review of the course of their practices. For the vocational training of continuing education projects. It was decided to obtain a research whose main objective is to formulate guiding principles for a continuing education in service of the university professor. To this end, theoretical dialogues were established with authors who discuss a universal teaching among them: Almeida, Canário, Cunha, Fusari, Garrido and Inbernón. In addition, based on a content analysis, four new records of university professors from a higher education institution in the South Zone of São Paulo, about their expectations and perceptions about the respect of continuing teacher education. It was concluded that teachers realize the importance of continuing education and have a space for collective reflection and exchange of experiences that includes the subjective tasks of teaching, a workplace approach to teaching and how to teach and how and learn and an occasion for recognition and investment by the institution. Based on literature and record analysis, students were inspired by new continuing education projects in higher education institutions.